Actual Use Behavior dalam Penggunaan QRIS pada UMKM di Kalurahan Sumberagung Menggunakan Pendekatan TPB - Gracia Barbara Dian Korina; Inna Zahara (Jurnal Riset Akuntansi, 2026)
The development of digital payment systems has encouraged the adoption of the Quick Response Code Indonesian Standard (QRIS) as an efficient and practical cashless payment method. This study aims to examine the influence of attitude toward behavior, subjective norm, and Perceived Behavioral Control on Behavioral Intention and Actual Use Behavior of QRIS among MSMEs in Sumberagung Village using the Theory of Planned Behavior (TPB). This study employs a quantitative approach with data collected through questionnaires distributed to MSME owners using QRIS. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that attitude toward behavior, subjective norm, and Perceived Behavioral Control have a positive and significant effect on Behavioral Intention. Furthermore, Perceived Behavioral Control and Behavioral Intention positively and significantly affect Actual Use Behavior. Behavioral Intention is also proven to mediate the relationship between attitude toward behavior, subjective norm, perceived behavioral control, and Actual Use Behavior. These findings indicate that Behavioral Intention is the primary factor influencing actual QRIS usage behavior among MSMEs.